Visitor-centric marketing approach driving theme park customer patronage: unveiling the post COVID-19 pandemic perspective / Nooraini Mohamad Sheriff ... [et al.] - Mohamad Sheriff, Nooraini; Sahak, Siti Zaleha; Raja Ezar Ishamuddin, Raja Noor Diyana; Sulaiman, Syahira Nadia (Universiti Teknologi MARA, Perlis, 2024)
The onset of Covid-19 pandemic has resulted in a drop in visitor ship and income causing many theme parks to fail in sustaining their business. In reciprocating to this pandemic, Malaysia's theme park industry, have become more innovative in adapting to this rapidly changing new norm. This research ascertained the influence of service quality, promotion and price on customer patronage of theme parks during Covid-19. Data were collected from 340 respondents. Convenience sampling technique was used to select the respondents and a close ended structured questionnaire with a 5-point Likert scale was used for data collection. Findings from this study revealed that pricing and service quality has a strong influence on theme park patronage. This calls for management of theme parks to innovate and redesign their service quality dimensions and conduct consistent training in theme park service quality delivery to familiarize service delivery employees of their roles in the service delivery process. Theme parks too should inject flexibility in their ticket pricing to make them affordable. Such visitor-centric marketing approach can drive customer satisfaction, create positive word-of-mouth among visitors to increase patronage to the theme park and eventually heighten profits.